Validation of a Deficit-Accumulation Frailty Index in the ASPirin in Reducing Events in the Elderly Study and Its Predictive Capacity for Disability-Free Survival. Issue 1 (2nd August 2021) - Ryan, Joanne; Espinoza, Sara; Ernst, Michael E; Ekram, A R M Saifuddin; Wolfe, Rory; Murray, Anne M; Shah, Raj C; Orchard, Suzanne G; Fitzgerald, Sharyn; Beilin, Lawrence J; Ward, Stephanie A; Williamson, Jeff D; et al.
Abstract: Frailty is a state of heightened vulnerability and susceptibility to physiologic stressors that increases with age. It has shown increasing utility in predicting a range of adverse health outcomes. Here, we characterize a 67-item deficit-accumulation frailty index (FI) in 19 110 community-dwelling individuals in the ASPirin in Reducing Events in the Elderly clinical trial. Participants aged 65–98 years were recruited from the United States and Australia and were without diagnosed dementia and cardiovascular disease, and major physical disability. The median FI score was .10 (interquartile range: .07–.14) at baseline, and the prevalence of frailty (FI > .21) increased from 8.1% to 17.4% after 6 years. FI was positively associated with age, and women had significantly higher scores than men at all ages. The FI was negatively correlated with gait speed ( r = −.31) and grip strength ( r = −.46), and strongly associated with a modified Fried's frailty phenotype ( p < .0001, for all comparisons). Frailty was associated with the primary composite outcome capturing independent life lived free of major disability and dementia, and increased the rate of persistent physical disability (hazard ratio: 21.3, 95% confidence interval: 15.6–28.9). It added significantly to the predictive capacity of these outcomes above age, sex, and ethnicity alone. The FI is thus a useful biomarker of aging even among relatively healthy older individuals and provides important information about an individual's vulnerability to and risk of disease.